Changes in substance use in relation to opioid agonist therapy among people who use drugs in a Canadian setting. (1st July 2020) - Dong, Huiru; Hayashi, Kanna; Milloy, M-J; DeBeck, Kora; Singer, Joel; Wong, Hubert; Wood, Evan; Kerr, Thomas
Highlights: Use of illicit opioids is significantly reduced with opioid agonist therapy. Concomitant use of cocaine and crack cocaine is highly prevalent. Problematic use of alcohol increases after initiating opioid agonist therapy. Tailored strategies are needed for poly-substance users accessing opioid treatment. Abstract: Background: Although previous studies have shown that opioid agonist therapy (OAT) is linked to reductions in illicit opioid use, less is known about how OAT impacts the use of other psychoactive substances. We aimed to examine the changes in use of different substances by comparing patterns before and after initiating OAT. Methods: Data for this study was derived from three ongoing prospective cohorts involving people who use drugs in Vancouver, Canada from 1996 to 2018. We assessed use patterns for heroin, illicit prescription opioid, cocaine, crack cocaine, crystal methamphetamine, cannabis, daily alcohol use, and benzodiazepines. Segmented regression was conducted to compare the trends of substance use between pre-treatment and post-treatment periods. Results: The study included 1107 participants. After OAT engagement, we observed an immediate decline in the proportion as well as a decreasing trend for heroin (Adjusted Odds Ratio (AOR): 0.80, 95% confidence interval (CI): 0.77, 0.83), illicit prescription opioid (AOR: 0.87, 95% CI: 0.83, 0.90), and benzodiazepines (AOR: 0.73, 95 % CI: 0.67, 0.80). There was no significant difference comparing the pre-treatment and post-treatment trends for cocaine, crack cocaine, crystal methamphetamine, and cannabis. However, higher growth slope was noted during the post-treatment period for daily alcohol use ( P = 0.016). Conclusions: We observed significant reduction in illicit opioids use following OAT initiation, but not for stimulant and cannabis. The increasing problematic use of alcohol may pose challenges to the safety and effectiveness of OAT. Development of comprehensive and tailored treatment strategies is needed for poly-substance users accessing OAT.